Kepedulian Masyarakat Muslim terhadap Makanan Halal di Daerah Minoritas (Studi Majelis Masjid Nurul Falah Kabupaten Tana Toraja) - Arnis Inrani Ibrahim; Riska Damayanti (STAI DDI Kota Makassar, 2021)
This research was conducted to find out the concern for halal food for the Nurul Falaq Mosque Assembly in Mengkendek District, Tana Toraja Regency. The method used by the researcher is aqualitative approach, namely receiving information in the form of data in the form of sentences or narratives. The data that has been obtained is thenanalyzed by descriptive analysis method. Furthermore, the researchers also conducted direct interviews with several members of the Nurul Falaq Mosque Council. The results of this study are that although the people of the Masjid Nurul Falaq Assembly live in Muslim minority areas, when they are going to consume products or food they always pay attention of the halalness of a productand be more careful in consuming food.